Water supply treatment sustainability of semambu water supply treatment process - water footprint approach - Edriyana, Abd Aziz; Syazwan, N. Moni; Marlinda, Abdul Malek; Iqmal, H. Hadi; Nabil F., Zulkifli (2017)
The Life Cycle Assessment (LCA) has long been used to assess the impact of products or services to the environment however recently Water Footprint Assessment (WFA) has been introduced. In this study, the assessment by using Water Footprint (WF) approach was conducted to assess water consumption within the water supply treatment process (WSTP) services of Semambu Water Treatment Plant (WTP). Identification of the type of WF at each stage of WSTP was carried out and later the WF accounting for the period 2010 – 2016 was calculated. Several factors that might influence the accounting such as population, and landuse. The increasing value of total WF per year was due to the increasing water demand from population and land use activities. However, the pattern of rainfall intensity from the monsoonal changes was not majorly affected the total amount of WF per year. As a conclusion, if the value of WF per year keeps increasing due to unregulated development in addition to the occurrences of climate changing, the intake river water will be insufficient and may lead to water scarcity. The findings in this study suggest actions to reduce the WF will likely have a great impact on freshwater resources availability and sustainability.